Therapeutic Potential of MgO and MnO Nanoparticles Within the Context of Thyroid Profile and Pancreatic Histology in a Diabetic Rat Model - Arslan Shaukat; Ghulam Hussain; Shahzad Irfan; Muhammad Umar Ijaz; Haseeb Anwar (SAGE Publishing, 2022)
Magnesium oxide (MgO) and manganese oxide (MnO) have been reported to be effective against Diabetes Mellitus (DM). However, their nanoparticulate form has not been evaluated for antidiabetic effect. MgO and MnO nanoparticles (15-35 nm) were synthesized and subsequently characterized by ultraviolet-visible spectroscopy (UV-VIS), zeta sizer, and scanning electron microscopy. 6-7 weeks old rats weighing 200-220 mg were divided into 07 equal groups (n = 8), namely, negative control (NC), positive control (PC), standard control (Std-C), MgO high dose group (MgO-300) and low dose group (MgO-150), and MnO nanoparticle high dose (MnO-30) and low dose group (MnO-15). Diabetes was chemically induced (streptozotocin 60 mg/kg B.W) in all groups except the NC. Animals were given CMD and water was ad libitum . Nanoparticles were supplemented for 30 days after the successful induction of diabetes. Blood and tissue samples were collected after the 30 th day of the trial. The mean serum glucose, insulin, and glucagon levels were improved maximally in the MgO-300 group followed by MgO-150 and MnO-30 groups. Whereas the MnO-15 group fails to show any substantial improvement in the levels of glucose, insulin, and glucagon as compared to the positive control group. Interesting the serum triiodothyronine, thyroxine, and thyroid-stimulating hormone levels were markedly improved in all the nanoparticle treatment groups and were found to be similar to the standard control group. These results highlight the modulatory properties of MgO and MnO nanoparticles and merit further studies delineating the molecular mechanisms through which these nanoparticles induce antidiabetic effects.